Enhancing Investment Literacy Level among people in Tasikmalaya - Peter Peter; Dini Iskandar; Martalena Martalena; Tedy Wahyusaputra; Herlina Herlina; Bram Hadianto (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Low investment literacy in the community can lead to society being exploited by fraudsters offering high returns for a short period, only to require the invested money later, as seen in some cases in Tasikmalaya. Therefore, socialization to open social minds is needed: The legal investment instruments are still in the capital market as alternatives. Moreover, this service community educates members of society in Tasikmalaya, specifically those affiliated with the Christian Education Agency Foundation, who serve as participants. Using a lecture-and-question-and-answer approach, this community service works. To test their comprehension, committee members shared a Google Form containing multiple-choice investment problems based on Lusardi and Mitchell (2009) to gather correct responses before and after the material presentation. After that, the proper responses are compared. As a result, the average correct answer ratio increases from 65.38% to 77.56% before and after material presentation, respectively. Therefore, community service effectively enhances their understanding of the subject matter. Through this activity, the risk of fraudulent investment can be significantly reduced, allowing people to choose a suitable instrument based on their risk profile, especially in Tasikmalaya.